Muslim CEO, women on boards and corporate responsibility reporting: some evidence from Malaysia - Alazzani, Absdulsamad; Wan Hussin, Wan Nordin; Jones, Michael John (Emerald Publishing Limited., 2019)
Purpose: Very limited research has been devoted to answering the question of whether the religious beliefs of the upper echelons of management and gender diversity have any impacts on the communication of corporate social responsibility (CSR) information in the marketplace. This study attempts to fill the void in the literature by posing the two research question: first, does the CEO religion affect a firm’s CSR behaviour?; second, do the women on the boards influence CSR reporting? Design/methodology/approach: We performed our tests on a sample of 133 firms listed in Bursa Malaysia that have analysts following using a self-constructed CSR disclosure index based on information in annual reports in 2009. Twenty three percent of our sample firms have Muslim CEOs, and women made up only 8% of board members. Findings: We find that Muslim CEOs are significantly associated with greater disclosure of CSR information. We also find only a moderate relationship between board gender diversity and CSR disclosure. This is probably due to insufficient number of women on boards. Limitations: The disclosure index is based on unsubstantiated CSR information provided in annual reports, and we examine only two aspects of board diversity namely Muslim religiousity and gender mix. Originality/value: This study advances the research on upper echelons theory by illuminating the importance of religious value in influencing the CSR behaviour of corporate leaders. This has been largely overlooked due to lack of data.